The Input Allocation and Potato Production on Small-Scale Farming in Pegunungan Arfak Regency - Pattiasina, Trees Augustine; Rita Nurmalina; Harianto; Anna Fariyanti (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Small-scale potato farming in the Arfak Mountains needs attention in allocating inputs for efficient farming. This study aims to describe the allocation of the use of potato farming inputs, analyze the factors that affect potato production, and analyze the level of technical efficiency of potato farming in the Arfak Mountains. Arfak Mountains Regency was chosen purposively as the research location. Data collection starts from December 2021 to February 2022. Sampling was done by snowball sampling with a sample of 140 respondents. The data used in this study is cross-section data which was analyzed using the Stochastic Frontier Cobb Douglas production function approach. The results showed that the average farmer in the Arfak Mountains controlled 0.07 hectares of land for potato farming, with a seed requirement of 22 kg per hectare. The factors that affect potato production are land, seeds, and female labor. The level of technical efficiency of potato farming is 73 percent. Improvements in farming management and extension assistance for good agricultural practices and the use of technology according to farmers' local wisdom need to be carried out to increase potato production and productivity. Keywords: local knowledge, low input, potato, small-scale farming, technical efficiency